The interaction between exchange rates and stock princes: An Australian context. - Richards, N.; Simpson, John; Evans, J. (2007)
The aim of this paper is to examine the interaction between stock prices and exchange rates in Australia. During the period of the study, the value of the stock market increased by two-thirds and the Australian dollar exchange rate appreciated by almost one-third. The empirical analysis employed provides evidence of a positive co-integrating relationship between these variables, with Granger causality found to run from stock prices to the exchange rate during the sample period. Although commodity prices have not been included, the significance of the results lends support to the notion that these two key financial variables interacted in a manner consistent with the portfolio balance model, that is, stock price movements cause changes in the exchange rate. This challenges the traditional view of the Australian economy as export-dependent, and also suggests that the Australian stock market has the depth annd liquidity to adequately compete for both domestic and international capital against other larger markets.